Monitoring of Insecticide Resistance in Anopheles culicifacies in Twelve Districts of Madhya Pradesh, Central India (2017–2019) - Ashok K. Mishra; Praveen K Bharti; Gyan Chand; Aparup Das; Himanshu Jayswar; Manju Rahi; Kamaraju Raghavendra (Journal of Tropical Medicine)
Background. Indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) are malaria vector control measures used in India, but the development of insecticide resistance poses major impediments for effective vector control strategies. As per the guidelines of the National Vector Borne Disease Control Programme (NVBDCP), the study was conducted in 12 districts of Madhya Pradesh to generate data on insecticide resistance in malaria vectors. Methods. The susceptibility tests were conducted on adult An. culicifacies as per the WHO standard technique with wild-caught mosquitoes. The blood-fed female mosquitoes were exposed in 3 to 4 replicates on each occasion to the impregnated papers with specified discriminating dosages of the insecticides (DDT: 4%, malathion: 5%, deltamethrin: 0.05%, and alphacypermethrin: 0.05%), for one hour, and mortality was recorded after 24-hour holding. Results. An. culicifacies was found resistant to DDT 4% in all the 12 districts and malathion in 11 districts. The resistance to alphacypermethrin was also observed in two districts, and possible resistance was found to alphacypermethrin in seven districts and to deltamethrin in eight districts, while the vector was found susceptible to both deltamethrin and alphacypermethrin in only 3 districts. Conclusion. An. culicifacies is resistant to DDT and malathion and has emerging resistance to pyrethroids, alphacypermethrin, and deltamethrin. Therefore, regular monitoring of insecticide susceptibility in malaria vectors is needed for implementing effective vector management strategies. However, studies to verify the impact of IRS with good coverage on the transmission of disease are required before deciding on the change of insecticide in conjunction with epidemiological data.